(untitled) (American Journal of Islam and Society, 2011)
Scott Siraj al-Haqq Kugle’s Homosexuality in Islam: Critical Reflection on Gay, Lesbian, and Transgender Muslims is a comprehensive, engaging, and original rereading of the formative Islamic texts and traditions. Targeted at both academic and popular readers, the book has two prime objectives: to push heterosexual Muslims to confront their own prejudices about homosexuality within the Muslim community, and to give lesbian, gay, and transgender Muslims greater confidence and the ability to speak about their sexual realities in regard to the Islamic intellectual tradition ...